AntiGQ1b antibody positive with MFS/GBS overlapped syndrome with diplopia and hemiplegia onset: Case report and retrospective analysis. Issue 37 (16th September 2022) - Zhao, Mingmin; Gu, Yuxuan; Zhao, Jingru; Li, Na
Abstract : Rationale: GBS and MFS have been divided into several subtypes, constituting a series of independent and overlapping syndromes that share similar pathophysiology, leading to common clinical features, including history of previous infection, single-phase course, symmetry, skull or limbs weakness, CFS albumin cell separation (high protein, normal cell count), antiganglioside antibodies and axon, or evidence of demyelinating neuropathy neurophysiology. Part of the MFS in patients with clinical manifestations may be complicated, and even symptoms are not typical. A few patients may overlap with BBE or GBS. Patient concerns: Most patients with MFS/GBS overlap syndrome have a good prognosis, and a few patients may experience fluctuations or re-exacerbations. In most patients, after treatment, their neurological function basically recovers within a few weeks or months. Diagnosis interventions: The patient had ophthalmoplegia, ataxia, weak force, and protein-cell separation in cerebrospinal fluid during the development of the disease. The diagnosis of MFS overlapped with typical GBS was considered. The CSF specific IgG oligoclonal zone and anti-Sulfatide antibody were positive. Anti-GT1a IgG was positive. Anti-GQ1b IgG was positive, which supported the diagnosis of GBS spectrum disorders. According to their common immunological basis, plasma exchange or intravenous immunoglobulin (IVIG) therapy is recommended, which can effectively improve the symptoms and shorten the course of the disease. Outcomes: After treatment with glucocorticoids and gamma globulin, the symptoms improved and the patient was discharged. Lessons: MFS/GBS Superimposed syndrome is a rare clinical disease. Therefore, more attention should be paid to early diagnosis and treatment of similar patients to avoid misdiagnosis. Cerebral spinal fluid (CFS) examination, neuroelectrophysiology, and GQ1b antibody detection can be used to confirm the diagnosis.